Time Between Start of Tacrolimus Use and Target Serum Level in Patients After Adult Liver Transplantation - Alves, Paola Hoff; Sampaio, Vittoria; Araújo , Alexandre de; Tortato, Caroline; Silva, Mário Reis Álvares da Silva (Brazilian Journal of Transplantation, 2022)
Introduction: Tacrolimus is one of the most used immunosuppressants in patients after liver transplantation and there is often a wide variation in its serum level. Assessing the mean time to reach the target serum level of tacrolimus after liver transplantation is critical, as very low levels increase with chances of graft rejection and very high levels are associated with toxicity. Methodology: Observational, retrospective cohort study conducted at Hospital de Clínicas de Porto Alegre. Liver transplant patients between December 2012 and December 2017 using oral tacrolimus were included. Patients who reached a serum level between 6–8 ng/mL during month 1 post-transplant were considered as target serum levels. Results: 78% (67/87) of patients reached the target serum level within 10 days after liver transplantation. Patients who experienced rejection over 1 year after transplantation took around 9 days to reach the target serum level during the index hospital stay. Patients who did not present rejection reached target serum level within 7 days after starting the immunosuppressant. Conclusion: Our work, considering therapeutic target values between 6–8 ng/mL in patients after immediate liver transplantation, demonstrated that this population performed a mean time that seems to determine a good prognosis, since in less than 2 weeks 78% of patients reached target serum level close to what was recommended.